Features of personnel management in the public service system of the republic of Kazakhstan - Kim, Yu.; Omarova, A. (KU Publ., 2021)
Object: It is a social relations, developing in the sphere of formation of the civil service in the Republic of Kazakhstan. National and other countries experience indicate that it is impossible to create an effective public service system without developing scientifically based and verified concepts and features of personnel management in the public service system, which would eliminate systemic contradictions in the legal regulation. The growth of scientific interest in the problems of theory and practice of public service has objective grounds of the study. Methods: Methods of grouping and classification, as well as methods of mathematical modeling, were used in the processing and systematization of data. An econometric model was constructed. Findings: While investigating the features of personnel management in the system of civil service of Kazakhstan, it was revealed that the civil service is based on certain principles, on the basis of which it is possible to carry out personnel planning to respond to changes in the needs of the public service. The authors hypothesized, there is a relationship between the indicator "Services in the field of public administration; services in the field of mandatory social security" and the factor "The list number of employees in the field, mandatory social security" and "The average monthly salary of civil servants". A regression analysis was performed to prove or disprove this hypothesis. Conclusions: Based on the analysis we can say with confidence, the hypothesis put forward about the relationship between the indicators in previous stage are confirmed. The authors comes to the conclusion that the staffing of civil servants is a necessary management process, since the effectiveness of the activities of public authorities is largely determined by the quantity and quality of resources for effective public administration.
Қазақстан Республикасының мемлекеттік басқару жүйесіндегі персоналды басқару ерекшеліктері
Особенности управления персоналом в системе государственной службы Республики Казахстан
Keywords: public service; civil service; governance; development strategy; staffing; communication; innovation; management